The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.3926/ic.2011.v7n1.p1-30
|View full text |Cite
|
Sign up to set email alerts
|

A study on intangible assets disclosure: An evidence from Indian companies

Abstract: Purpose: India has emerged at the top of the pedestal in the present knowledge-driven global marketplace, where intangible assets hold much more value than physical assets. The objective of this study is to determine the extent of intangible asset disclosure by companies in India Design/methodology/approach: This study relates to the years 2003-04 and 2007-08 and is based on 243 companies selected from BT-500 companies. The annual reports of these companies were analyzed using content analysis so as to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 17 publications
1
9
0
3
Order By: Relevance
“…Our results agree in part with those of Chander and Mehra (2011). For a sample of companies in India they find a low level of disclosure of intangible assets but improving from 2003-4 to 2007-8, the most disclosed items being those mandatory and those showing greater competitive advantage.…”
Section: Discussion Of the Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Our results agree in part with those of Chander and Mehra (2011). For a sample of companies in India they find a low level of disclosure of intangible assets but improving from 2003-4 to 2007-8, the most disclosed items being those mandatory and those showing greater competitive advantage.…”
Section: Discussion Of the Resultssupporting
confidence: 88%
“…Today, increasing weight is given to providing information on human capital (HC), also within the context of Corporate Social Responsibility (CSR). Yet companies do not offer their interest groups detailed information on human resources, because they do not give proper credit to the value of such disclosure (Chander & Mehra, 2011;Gamerschlag, 2013).…”
Section: Human Capital Information In Management Reportsmentioning
confidence: 99%
“…We highlighted that only 44 firms mentioned R&D expenses in their footnotes and/or declared investing in R&D in the period, pointing out the importance of better disclosure practices. Chander and Mehra (2011) affirm that intangible assets became a key part of the process of value creation for any firm, requiring external communication to the stakeholders. In addition, Silva, Klotzle, Pinto, and Motta (2018) found evidence that firms which provide more information to the market about their innovation projects tend to mitigate their potential undervaluation in, approximately, 40%.…”
Section: Introductionmentioning
confidence: 99%
“…Following on from the useful information index, we find the indexes corresponding to the three classic categories of the study of intellectual capital: human, relational, and structural capital that in our study occupy second, third and last place respectively. The importance of external intangible assets, the relational block, is also relevant and occupies first place in the Chander and Mehra (2011) study. According to Ferreira et al (2017), the relevance of human capital is confirmed in f annual reports, because corporate websites confirm the prevalence of relational capital.…”
Section: Discussionmentioning
confidence: 99%